Mercury and lead legacy pollution from a coal-fired power plant recorded in lake Chiprana sedimentary record (NE Spain) - Isabel Rodriguez-Veiga; Jorge Pey; Antonio Garralón; Blas L. Valero-Garcés; Thomas Schmid; Alfonso Saiz-Lopez; Connor Doyle; Stefan Schröder; Virginia Peyres; Marcos Mejuto; Miguel Ángel Lominchar; Marcel-Saïd Galofré Penacho; et al. (Journal of Soils and Sediments, 2026)
Purpose The Ebro Basin is one of the most industrialised regions of the Iberian Peninsula, yet its long-term legacy of metal contamination remains poorly constrained due to the scarcity of continuous sedimentary archives in semi-arid environments. This study reconstructs the history of mercury (Hg) and lead (Pb) pollution in the Ebro Basin using Lake Chiprana, the only permanent hypersaline lake providing a continuous, high-resolution sedimentary record in this region. Methods A dated sediment core covering the last ~ 250 years was analysed for Hg and Pb concentrations, enrichment factors, accumulation fluxes and Pb isotopic composition. To link historical contamination with present-day processes, sedimentary data were directly compared with contemporary atmospheric deposition measured by bulk collectors located 5 km from the lake. Geochemical, isotopic and source-apportionment approaches were integrated. Results The sedimentary record shows an increase in Hg and Pb accumulation during the mid-twentieth century, contemporaneous with the operation of a nearby coal-fired power plant. Hg and Pb enrichment factors and accumulation fluxes increased between 1950 and 1980, providing evidence of local coal combustion supported by Pb isotopic signatures. In contrast, recent decades are characterised by lower fluxes and by a clearer expression of mixed sources, including regional dust inputs, Saharan dust, biomass burning, traffic-related emissions and regional dust resuspension. Conclusion The close agreement between recent sedimentary accumulation rates and modern atmospheric fluxes demonstrates the reliability of lake sediments as integrative monitors of pollution legacy in industrialised semi-arid regions. Lake Chiprana emerges as a key reference archive for assessing long-term Hg and Pb contamination and for disentangling historical and contemporary sources affecting soils and sediments in Southern Europe.

Production of a chiral alcohol, 1-(3,4-dihydroxyphenyl) ethanol, by mushroom tyrosinase - Sarah J. Brooks; Jasmina Nikodinovic; Leona Martin; Evelyn M. Doyle; Timothy O’Sullivan; Patrick J. Guiry; Lydie Coulombel; Zhi Li; Kevin E. O’Connor (Biotechnology Letters, 2013)